Pemanfaatan Simulasi Jarnigan Komunikasi Vehicle-to-Everything (V2X) untuk Sistem Transportasi Cerdas: Literature Review - Ni Putu Amanda Saraswati; Ngurah Indra ER; I Nyoman Satya Kumara (Majalah Ilmiah Teknologi Elektro, 2025)
The increasing number of vehicles has led to several complex challenges, such as traffic congestion, air pollution, and safety driving issues. These challenges also result in economic losses. Fortunately, with the advance in technologies today, we can utilize Intelligent Transportation Systems (ITS) to establish a system that is more efficient, safer, and environmentally friendly. Specifically, the concept of Vehicle-to-Everything (V2X) has emerged as a potential solution to address various road-related challenges. However, the real-world implementation of V2X still faces numerous obstacles, particularly in terms of cost and safety concerns. Deploying V2X on a large scale requires significant investments due to the need for communication infrastructure and hardware development. Therefore, simulation can serve as an initial solution to tackle these challenges. Simulations make it possible to set up different communication network protocols and architectures and to model different traffic conditions without the risks that come with testing in the real world. In this review paper, we aim to give a clearer insight into the trends, challenges, and opportunities of V2X simulations in various traffic environments.